Efficacy and costs of a workplace wellness programme. (8th December 2020) - Rezai, R; SantaBarbara, N; Almirol, E; Shedd, K; Terry, E; Park, M; Comulada, W S
Abstract: Background: Research investigating the efficacy of workplace wellness programmes to promote exercise, and by extension, reduce obesity and increase productivity has proliferated in recent years. Although preliminary work is encouraging, more work is needed. Aims: To evaluate the effects and overall cost of a workplace exercise programme on multiple physical outcomes, including body mass index, aerobic fitness and muscular fitness. Methods: Data from the Bruin Health Improvement Programme .5 (BHIP) between August 2013 and July 2018 were analysed. BHIP is a 12-week workplace wellness programme that assesses multiple areas of physical and mental health. For this study, changes in weight, waist-to-hip ratio, aerobic fitness and muscular endurance were analysed using paired samples t -tests and chi-squared tests. Using results from a prior analysis of Medical Expenditure Panel Survey, the estimated medical expenditure savings associated with weight loss were also analysed. Results: A total of 518 participants (84% female) took part in the BHIP programme (mean age = 41 years, SD = 1.17). There were significant decreases in all anthropometric indices and significant increases in all fitness outcomes ( P < 0.01) from baseline to follow-up. Estimated programme cost per participant, per session was 473 US Dollars (USD), and weight loss is estimated to reduce annual medical care costs by 2200 USD. Conclusions: Results showed significant improvements in all physical outcomes of interest. Additionally, there appears to be an inverse relationship between improvements in employee health and employer healthcare costs. Strengths, limitations and future directions are discussed.